Design and implementation of RESCUR in Sweden for promoting resilience in children: a study protocol - Charli Eriksson; Birgitta Kimber; Therése Skoog (BMC, 2018)
Abstract Background This research program aims to investigate the implementation and effects of a theoretically promising prevention method. It is being developed in a European research collaboration within a Comenius project (2012-2015) between 6 European universities (in Malta, Italy, Greece, Croatia, Portugal and Sweden) with the purpose of enhancing European children's resilience. Methods/design RESCUR in Sweden consists in a RCT study of the Resilience Curriculum (RESCUR) that is taking place in Sweden 2017-2019. The study is being performed by Junis, IOGT-NTO's Junior Association, part of IOGT International, in conjunction with researchers at Göteborg, Umeå and Stockholm universities, and is being funded by the Public Health Agency of Sweden. Around 1000 children of the ages 7-12 will, through their schools and associations, or via groups in social services, be acquainted with the material. Children will learn and practice mindfulness, storytelling, group discussions and much more, all designed to strengthen protective factors and increase their resilience. The program also involves parents, who are taking part in the work to reinforce children's protective factors. Based on the work with groups of children, an effectiveness study including children aged 7-12 in school classes, with randomized and controlled pre- and post-measurements, self-rating questionnaires and group observations is being performed. The program will also be implemented in a non-governmental organization and in groups in social services. The study also investigates forms of implementation. Discussion The design of the study will enable the researchers to answer five research questions by using a mixed-methods approach. Implementation will be studied, which is a necessary prerequisite for an effect study. Moreover, the research procedure has been tailored to the target group, with age-appropriate measures as well as multiple informants, which will produce high-quality data for analysis. A special ethical challenge is the study of young children, and efforts to give children a voice have been included in the program. This project is regarded as having good potential to benefit children in general, and particularly children in vulnerable positions. Trial registration National Institute of Health, ClinicalTrials.gov identifier NCT03655418. Registered August 31, 2018.